Teaching Writing Effectively: A Case Study in Junior High Schools - Situmorang, Hotma Uli; Situmorang, Artania; Limbong, Yohana Dona Vika (English Language in Focus (ELIF), 2024)
AbstractThis article reports a study of what methods are used by English teachers in teaching writing to junior high school students. This research uses a qualitative case study research design. The data was obtained from the instrument, namely teacher interviews by distributing online questionnaires. Many findings indicate that the learning program is successful in improving students' rewriting skills. In particular, they have shown some improvements to schema structure, grammatical roles, and graphical features. The meaning of this study is that students and teachers have additional learning/teaching talents, including : (1) increasing students' motivation to participate in writing classes, (2) helping students build their writing, (3) helping students solve their problems, (4 ) provide a way for students to be creative or interact with friends and (5) help students summarize and think clearly. From these findings, it is confirmed that the strategies in the research are applied in written teaching.